Anak the movie - Santos, Vilma; Barreto, Claudine; Torre, Joel; Quintos, Rory B. (Star Cinema, 2003)
Anak is the story of a mother's agony and her desperate attempt to piece back the broken fragments of her shattered family after years of working abroad under abusive conditions in order to provide a better life for her family.